IJTIHAD AL-ILMI AL-‘ASHRI: MODERN SCIENTIFIC IJTIHAD (Mazahib, 2007)
All problems faced by Muslim in the contemporary life must be answerable in Islamic law. The Koran and the Prophet tradition have given general principles in many aspects so that it is untenable to say that there is no answer for a problem. In addition, the development of Islamic studies has opened the opportunity for nowadays Muslim to carry out ijtihad either individual ijtihad, collective ijtihad or thematic ijtihad. Yet, in order to realize this, Muslims have to study classical Islamic jurisprudence critically. This is done by studying a thought contextually, i.e. by carefully examining where and when an Islamic scholar lived.